2019
DOI: 10.7199/ped.oncall.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood Thyroid Stimulating Hormone Level - and the influence of perinatal and other factors on it

Abstract: Background: Thyroid hormone is essential for growth and development especially the brain. Deficiency of thyroid hormone i.e. congenital hypothyroidism (CH) is the commonest cause of preventable mental retardation. As it is difficult to diagnose CH with clinical symptoms at birth, most patients with CH are diagnosed by laboratory results. Early detection is important, either by Thyroid Stimulating Hormone (TSH) or T4 estimation or both by newborn screening. Cord blood TSH (CB-TSH) estimation has high sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Cortés-Castell et al (31) have reported the risk of high neonatal TSH without congenital hypothyroidism is higher in males. Although paralleled results have been extracted by other studies (13,32), several reports emphasized on no signi cant association of mean cord blood TSH and sex (1,24,25,33). However, the exact mechanism is not clear yet.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Cortés-Castell et al (31) have reported the risk of high neonatal TSH without congenital hypothyroidism is higher in males. Although paralleled results have been extracted by other studies (13,32), several reports emphasized on no signi cant association of mean cord blood TSH and sex (1,24,25,33). However, the exact mechanism is not clear yet.…”
Section: Discussionsupporting
confidence: 54%
“…Umbilical cord blood TSH measurement has shown several advantages, including non-invasive, easy sampling, and recheck enabling even before the mother leaves the hospital. However, some studies have demonstrated that the values for CBTSH can be affected by a variety of maternal neonatal factors, while these reports were accompanied by paradoxical and different results (1,3,13,19). In this study, the data of effect of maternal and neonatal factors on cord blood Free T4 and TSH were demonstrated, which were studied in neonates born at Amir-Al-Momenin, Semnan, Iran.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Seventy-nine studies were included in the systematic review, and 70 studies in the meta-analysis. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 The flow...…”
Section: Resultsmentioning
confidence: 99%